Cover image. Issue 1 (20th January 2023) - Redman, Kirsten N.; O'Brien, Katie E.; Ruiz, Francieli S.; Rae, Dale E.; Gómez‐Olivé, F. Xavier; von Schantz, Malcolm; Scheuermaier, Karine
Abstract : The cover image is based on the Original Article Delayed circadian rhythms in older Africans living with human immunodeficiency virus (HIV) by Kirsten N. Redman et al., https://doi.org/10.1111/jpi.12838 . Image Credit: Oriol Gómez‐Olivé, Karine Scheuermaier, Katie O'Brien.